Flexible hybrid graphene-based NFC tag antenna for temperature monitoring application - Mohd Faudzi, Najwa; Razali, Ahmad Rashidy; Abd Manaf, Asrulnizam; Abd Rahman, Nurul Huda; Ab Aziz, Ahmad Azlan; Hafiz, Syed Muhammad; Sulaiman, Suraya; Rashid, Nora’zah Abdul; Ibrahim, Amirudin; Mozi, Aiza Mahyuni (Institute of Advanced Engineering and Science, 2025)
A hybrid graphene-based material, composed of reduced graphene oxide (rGO) and silver nanoparticle (AgNP), has been proposed for a near field communication (NFC) tag antenna with an integrated, flexible temperature monitoring circuit. The limited availability of high-conductivity graphene-based materials in the market has restricted the use of graphene in NFC tag applications. Therefore, this paper proposes a hybrid graphene-based composition featuring a high conductivity of 3.95×106 S/m. The feasibility of this material for NFC tags had not been validated previously, which is the main motivation for this research. The synthesis of the materials, along with the design, fabrication, and characterization of the NFC tag, is also presented. Results show that the inkjet-printed tag achieves a good reading range of up to 3 cm and demonstrates robustness against bending from 60⁰ to 190⁰, maintaining a maximum reading range of 1.3 cm. Performance on various materials, such as plastic, paper, and carton, also shows minimal impact on frequency shifting. Additionally, the graphene-based NFC tag integrates well with the temperature circuit, effectively monitoring temperatures in the 20-60 ⁰C range in real-time. This makes the developed tag suitable for applications such as food safety monitoring systems through NFC-integrated packaging.